DEVELOPMENT OF A MULTIPLE MARKING SYSTEM ON SHOELAST: AN EFFICIENT AND ADAPTIVE SOLUTION FOR MULTI-DESIGN PRODUCTION - Umi Ramadhanti; Nunik Purwaningsih (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2025)
The lasting process in the footwear industry is essential for ensuring the accuracy and symmetry of upper placement on the shoelast, which directly affects the final shape and quality of the shoe. In many footwear industries, shoelasts are used without placement guides, leading operators to rely on visual estimation. This condition reduces accuracy, increases defects, and lowers efficiency, particularly when a single shoelast is used for multiple designs. This study aims to develop an adaptive and easily implemented multiple marking system on shoelasts to support various women’s footwear designs. The research combines needs analysis through observation of the lasting process with experimental testing of marking creation and application. Markings were designed based on upper dimensions, distinguished by color for each design, and applied using durable yet non-permanent acrylic markers. Testing on two shoe articles (A and B) evaluated upper-position accuracy, lasting time, and operator responses. Results indicate that the multiple marking system significantly improves accuracy in upper placement and reduces lasting time from 8–10 minutes to 5–7 minutes. Operators reported clearer guidance and easier adaptation. Limited production trials further showed defect reduction for article A from 18% to 10% and for article B from 28% to 8%. Overall, the study demonstrates that an adaptive multiple marking system on the shoelast is an effective and economical method to enhance accuracy, improve lasting performance, reduce defects, and maintain flexibility for multi-design footwear production.